SPIRITUAL AND MORAL DEVELOPMENT OF STUDENT YOUTH IN TODAY’S REALITIES - Sapozhnykov Stanislav (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article analyses scientific studies devoted to the problem of spiritual and moral development of student youth, provides their social and psychological characteristics, highlights the process of forming their moral values in today’s realities through the prism of Ukraine’s European integration aspirations, and proves the need for their comprehensive research due to the contradictions found. The purpose of the article is to identify existing contradictions and define the main theoretical problems of the spiritual and moral development of modern student youth, taking into account their social and psychological characteristics, to carry out a theoretical analysis of the concepts of “spirituality”, “value”, “value orientations”, “moral values”, “morality”, to investigate their main functions, and to provide the author’s definition of the process of spiritual and moral development of current student youth. The concept of “value” is analysed through the prism of philosophical approaches, studied from the psychology, sociology, and pedagogy viewpoints. The main functions of morality have been defined, and the concept of “moral values” is thoroughly scrutinized, which is also considered from the sociology, psychology, and pedagogy standpoints. The author’s definition of the processes of students’ spiritual and moral development and the formation of their moral values has been given. The process of moral values formation is considered a procedure of normalization based on the internalization of primary values and goals by young people. The spiritual and moral development of student youth is characterized as the course of implementing the consistent and purposeful improvement of the value-meaning sphere of their personality during socialization, the formation of ability to evaluate and consciously build universal moral ideals and values based on morality, as well as the proper attitude towards oneself and other people, to the state, and to the world as a whole. It has been emphasized that the formation of students’ moral values is a systematic process of a person’s development and self-development. At the same time, moral upbringing is an integral part of education, which ensures a relatively meaningful and purposeful upbringing of a person following the specifics of the goals, groups and organizations in which it is carried out. It has been found out that the main focus of the teacher’s activity should be the formation of moral values, and the main goal has to be the development of the child’s personality, capable of conscious and responsible choices of behaviour and actions in various life situations, without violating universal and generally significant values. The main theoretical issues for the formation of moral values in student youth have been identified. They include the problem of mutual coordination of upbringing influences of teachers and parents on student youth during their socialization and individualization; filling the methods of formation of educational activity with the appropriate moral content; the functioning of the relationship and mutual influence of personal qualities of student youth, which are in the stage of their formation; and creation of an effective model for the shaping of moral values in student youth taking into account the sequence of development of various personality qualities. It has been argued that the spiritual and moral development of student youth is not a common goal that can be achieved in a certain period with the assistance of specific means. The result of this process should be the formed morality of the individual, which can be defined as the highest goal that enables the existence of all other goals and is at the basis of human activity itself. It has been concluded that the formed morality of student youth can be considered not as a goal, but as an ideal – a regulatory principle and scale of assessment of their behaviour.